Stable matter-wave solitons in the vortex core of a uniform condensate - Adhikari, S. K. [UNESP] (IOP Publishing, 2015)
We demonstrate a stable, mobile, dipolar or nondipolar three-dimensional matter-wave soliton in the vortex core of a uniform nondipolar condensate. All intra- and inter-species contact interactions can be repulsive for a strongly dipolar soliton. For a weakly dipolar or nondipolar soliton, the intra-species contact interaction in the soliton should be attractive for the formation of a compact soliton. The soliton can propagate with a constant velocity along the vortex core without any deformation. Two such solitons undergo a quasi-elastic collision at medium velocities. We illustrate the findings using realistic interactions in a mean-field model of binary 87Rb-85Rb and 87Rb-164Dy systems.
Keywords: cold atoms; dipolar atom; mean-field model; soliton; vortex